L-Arginine and Cardioactive Arginine Derivatives as Substrates and Inhibitors of Human and Mouse NaCT/Nact - Surrer, Daniela; Fromm, Martin; Maas, Renke; König, Jörg (Metabolites, 2022)
The uptake transporter NaCT (gene symbol SLC13A5) is expressed in liver and brain and important for energy metabolism and brain development. Substrates include tricarboxylic acid cycle intermediates, e.g., citrate and succinate. To gain insights into the substrate spectrum of NaCT, we tested whether arginine and the cardioactive L-arginine metabolites asymmetric dimethylarginine (ADMA) and L-homoarginine are also transported by human and mouse NaCT/Nact. Using HEK293 cells overexpressing human or mouse NaCT/Nact we characterized these substances as substrates. Furthermore, inhibition studies were performed using the arginine derivative symmetric dimethylarginine (SDMA), the NaCT transport inhibitor BI01383298, and the prototypic substrate citrate. Arginine and the derivatives ADMA and L-homoarginine were identified as substrates of human and mouse NaCT. Transport of arginine and derivatives mediated by human and mouse NaCT were dose-dependently inhibited by SDMA. Whereas BI01383298 inhibited only human NaCT-mediated citrate uptake, it inhibits the uptake of arginine and derivatives mediated by both human NaCT and mouse Nact. In contrast, the prototypic substrate citrate inhibited the transport of arginine and derivatives mediated only by human NaCT. These results demonstrate a so far unknown link between NaCT/Nact and L-arginine and its cardiovascular important derivatives.
CRIS-Team Scopus Importer:2022-04-15
Keywords: arginine derivatives; cardioactive arginine metabolites; L-arginine; transport inhibition; uptake

Transport of aromatic amino acids l-tryptophan, l-tyrosine, and l-phenylalanine by the organic anion transporting polypeptide (OATP) 3A1 - Surrer, Daniela; Schüsser, Sarah; König, Jörg; Fromm, Martin; Geßner, Arne (Febs Journal, 2024)
Amino acids are important for cellular metabolism. Their uptake across the plasma membrane is mediated by transport proteins. Despite the fact that the organic anion transporting polypeptide 4C1 (OATP4C1, Uniprot: Q6ZQN7) mediates transport of l-arginine and l-arginine derivatives, other members of the OATP family have not been characterized as amino acid transporters. The OATP family member OATP3A1 (gene symbol SLCO3A1, Uniprot: Q9UIG8) is ubiquitously expressed in human cells and highly expressed in many cancer tissues and cell lines. However, only a few substrates are known for OATP3A1. Accordingly, knowledge about its biological relevance is restricted. Our aim was to identify new substrates of OATP3A1 to gain insights into its (patho-)physiological function. In an LC-MS-based untargeted metabolomics assay using untreated OATP3A1-overexpressing HEK293 cells and control cells, we identified several amino acids as potential substrates of OATP3A1. Subsequent uptake experiments using exogenously added substrates revealed OATP3A1-mediated transport of l-tryptophan, l-tyrosine, and l-phenylalanine with 194.8 ± 28.7% (P < 0.05), 226.2 ± 18.7% (P < 0.001), and 235.2 ± 13.5% (P < 0.001), respectively, in OATP3A1-overexpressing cells compared to control cells. Furthermore, kinetic transport parameters (Km values) were determined (Trp = 61.5 ± 14.2 μm, Tyr = 220.8 ± 54.5 μm, Phe = 234.7 ± 20.6 μm). In summary, we identified the amino acids l-tryptophan, l-tyrosine, and l-phenylalanine as new substrates of OATP3A1. These findings could be used for a better understanding of (patho-)physiological processes involving increased demand of amino acids, where OATP3A1 should be considered as an important uptake transporter of l-tryptophan, l-tyrosine, and l-phenylalanine.
CRIS-Team Scopus Importer:2024-09-06
Keywords: amino acids; cancer; OATP3A1; transporter; tryptophan